BANDAPEDIA SEBAGAI MEDIA EDUKASI WISATA DI BANDA NAIRA: Penguatan Kesadaran Sejarah Melalui Kolaborasi Mahasiswa dan Komunitas Lokal di Kepulauan Banda - RESTIANI; MUHAMMAD FARID (LPPM Universitas Banda Naira, 2026)
Banda Naira is a historically significant region that has played a crucial role in the global spice trade network since the sixteenth century and preserves various colonial and national historical heritage sites. Despite its considerable potential as a historical tourism destination, the utilization of cultural heritage in this region still faces several challenges, particularly the limited availability of historical interpretation media and the relatively low level of community involvement in managing local historical narratives. This article aims to analyze the role of collaboration between university students and local communities in enhancing historical awareness while developing BandaPedia as an educational platform for history and tourism in Banda Naira. This community engagement program employed a participatory action research (PAR) approach, emphasizing active community participation in identifying local potentials, collecting historical narratives, developing digital educational media, and conducting collective reflections on the outcomes of the program. The activities involved students from several universities and local community groups through community discussions, documentation of historical sites, and heritage walking tours. The findings indicate that participatory collaboration between students and local communities contributes significantly to strengthening historical awareness and encourages the production of community-based historical knowledge. Furthermore, the development of the BandaPedia platform demonstrates strong potential as a public history medium that supports historical interpretation, public education, and sustainable historical tourism promotion through digital heritage initiatives in Banda Naira.